2014
DOI: 10.1021/nl4040847
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Phase-Pure InAs Nanowires on Si(111) by Diminishing the Diameter to 10 nm

Abstract: Here we report the growth of phase-pure InAs nanowires on Si (111) substrates by molecular-beam epitaxy using Ag catalysts. A conventional one-step catalyst annealing process is found to give rise to InAs nanowires with diameters ranging from 4.5 to 81 nm due to the varying sizes of the Ag droplets, which reveal strong diameter dependence of the crystal structure. In contrast, a novel two-step catalyst annealing procedure yields vertical growth of highly uniform InAs nanowires ∼10 nm in diameter. Significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 50 publications
2
93
1
Order By: Relevance
“…On the basis of the highresolution transmission electron microscope imaging and corresponding reciprocal lattice spots extracted by fast Fourier transform, the NW has a catalyst/NW interface orientation relationship of cubic AuGa 2 {111}|cubic GaSb{111}, without any noticeable amount of crystal defects such as stacking faults or inversion domains, and so on. The grown NWs have the dominant growth axis of o1114 as this growth direction involves the lowest free energy crystal planes and thus are more thermodynamically favourable 35,36 , while a small amount of NWs with o1104 direction are also observed, which is probably induced by the defect formation in the initial stage of the NW growth, favouring the next higher index directions 17 . The AuGa 2 catalyst is then verified by the EDS results (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the highresolution transmission electron microscope imaging and corresponding reciprocal lattice spots extracted by fast Fourier transform, the NW has a catalyst/NW interface orientation relationship of cubic AuGa 2 {111}|cubic GaSb{111}, without any noticeable amount of crystal defects such as stacking faults or inversion domains, and so on. The grown NWs have the dominant growth axis of o1114 as this growth direction involves the lowest free energy crystal planes and thus are more thermodynamically favourable 35,36 , while a small amount of NWs with o1104 direction are also observed, which is probably induced by the defect formation in the initial stage of the NW growth, favouring the next higher index directions 17 . The AuGa 2 catalyst is then verified by the EDS results (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Phasepure nanowires of substantial length have been grown using Metal-Organic Chemical Vapour Deposition (MOCVD) [6] and Molecular Beam Epitaxy (MBE) [7]. These phase-pure nanowires have since been used to study how crystal phase influences the electronic [11,12], optical [13] and thermal properties [14].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Apparently, high crystal quality along an entire nanowire is indispensably desired to precisely define a DQD and thus a spin qubit in the nanowire. Single-crystal pure-phase InAs nanowires have been grown by molecular beam epitaxy (MBE) 16 and these nanowires manifest their high crystal quality by excellent performance in the field-effect transistors made from them. 17,18 In this letter, we report on realization of highly tunable DQD devices from single-crystal pure-phase InAs nanowires using the local finger gate technique and on measurements of the electron transport characteristics of the devices.…”
mentioning
confidence: 99%
“…It has been found that the InAs nanowires grown by MBE with small diameters (< 50 nm) are in pure phase and are either single wurtzite or single zincblende crystals, free from stack faults and extended defects. 16 The device fabrication begins from preparation of finger gate arrays on a silicon substrate covered with a 200-nm thick layer of SiO2. Each array contains seven finger gates labeled as G1 to G7 from 3 / 15 left to right (see Fig.…”
mentioning
confidence: 99%